FACTORS AFFECTING THE ADHERANCE OF POST CABG PATIENTSIN CARDIAC REHABILITATION-A CROSS-SECTIONALSTUDY IN KARACHI - Muniba Khanum et al (Baqai Journal of Health Sciences)
Cardiovascular disease (CVD) is the principal cause of death globally. To decrease this mortality rate, a wide-ranging program from hospital discharge to highly structured and monitored exercise therapy is required. Cardiac Rehabilitation (CR) purposes to decrease risks, disability, augment emotional welfare, to implement and follow healthy behavior, thus adopting a healthy life style. This study was aimed to determine the factors that affect adherence of post coronary artery bypass grafting (CABG) patient`s to Cardiac Rehabilitation. This cross-sectional study was conducted on 255 Post CABG patients with age 30 years above. Patients in Phase II and III of CR were interviewed through self-designed structured questionnaire. After taking the informed Consent during their hospital visit in eight hospitals in Karachi. Questioner was self-design structured questions with responses on Likert Scale. Patients in phase I of CR, patients in fitness program, pregnant females, Patients with disability, severe functional impairment and co-morbidities that limit CR participation were excluded. The collected data were entered in and analyze by the Statistical Package for Social Sciences version 20.0 Software (SPSS Inc., Chicago, Illinois). Frequencies and percentages were taken out for all qualitative variables and presented in tabular form. Most patients were referred for CR by the cardiologist (51.0%). A major factor that leads to non-adherence were distance to CR facilities (83.75%), fatigue (83.55%), lack of time (67.8%), lack of transport (62.7%). Other significant factors were illiteracy (42%), financial issues (63.9%), low self-efficacy (64%), lowlevel of physical fitness (39.6%). Adherence to Phase-II- CR was 52.2%, with no significant differences between men and women. Adherence was observed in patients who have accepted their condition (81.1%), learned to cope with the limitations (76.8%), were comfortable with exercise regime (67.4%), believed that exercise will decrease the deconditioning (74.9%) and will improve physical fitness (20.8%). Major